Ferroelectric-gated MoSe2 photodetectors with high photoresponsivity. (21st November 2022) - Yan, Qijie; Cheng, Jiaxin; Wang, Weike; Sun, Mengjiao; Yin, Yanling; Peng, Yuehua; Zhou, Weichang; Tang, Dongsheng
Abstract: Ferroelectric transistors with semiconductors as the channel material and ferroelectrics as the gate insulator have potential applications in nanoelectronics. We report in-situ modulation of optoelectronic properties of MoSe2 thin flakes on ferroelectric 0.7PbMg1/3 Nb2/3 O3 –0.3PbTiO3 (PMN-PT). Under the excitation of 638 nm laser, the photoresponsivity can be greatly boosted to 59.8 A W −1 and the detectivity to 3.2 × 10 10 Jones, with the improvement rates of about 1500% and 450%, respectively. These results suggest hybrid structure photodetector of two-dimensional layered material and ferroelectric has great application prospects in photoelectric detector.